Analisa Tingkat Kematangan Sistem Informasi Pada Costomer Service Menerapkan Framewordk Cobit 4.1 - Muhammad Zaki; Besus Maula Sulthon (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
Analysis of the Maturity Level of Information Systems at Costomer Service at PT Metrox Fortuna With Cobit 4.1 Framework. PT Metrox Fortuna is a retail retail company engaged in the fashion and lifestyle sector that focuses on the upper middle class market since 2004. This company utilizes information technology in managing its business processes, one of which is the management of service information systems. The application used as a payment information system is Enterprise Resource Planning (ERP). The problem found in the governance of the information system is that it is not optimal in using information technology systems effectively and efficiently, so that business needs have not reached the maximum and the company has not maximized the potential of each employee so that there is still a critical dependence on key individuals. Based on the results of research using the COBIT 4.1 framework, the current maturity level is 3.85 from the expected maturity level of 4, so there is a gap or average gap of 0.15. So there are several recommendations that can be applied to PT Metrox Fortuna. Several recommendations were made, namely the need for management to evaluate the training methods communicated to system users according to the standards needed to meet organizational goals and deliver the training intensively, the need for documented knowledge sharing and the provision of staff reserves